PENGARUH MODEL PEMBELAJARAN BERBASIS MASALAH TERHADAP MOTIVASI BELAJAR DAN PEMAHAMAN KONSEP SISWA KELAS VIII SMPN 2 TANJUNG - Sadrin, Sadrin; Gummah, Syifa’ul; Safitri, Baiq Rina Amelia (Lensa : Jurnal Kependidikan Fisika, 2015)
The research is aimed to find out the influence of Problem Based Learning toward students’ learning motivation and concept understanding at the VIII grade students of SMPN 2 Tanjung. The type of this research is Quasi-Experiment in which the researcher uses pretest-postest control group design. The population of this research is the whole VIII Grade students of SMPN 2 Tanjung which consists of 124 students. Simple random sampling was used to take the sample from the number of population. Two classes of the VIII Grade students were taken as the sample of the research. The two classes are VIIIB and VIIIC classes that each class consists of 30 students. Collecting the data needed in the study, the researcher uses test as the main instrument to collect the data needed in this study. The collected data of the research in analyzed by using statistical analysis method, t-test in particular. The result of data analysis shows that the t-test for students’ learning motivation is 2.318 and the value of t-table is 2,002 meanwhile the result of t-test for students’ concept understanding is 4.152 and the value of t-table is 2.002 at the level of significance 5%. It means that the result of t-test is higher than the value of t-table. It can be interpreted that the alternative hypothesis ( ha ) is accepted and the null hypthesis (ho) is rejected. Finally, the study concluded that there is significant influence of Problem Based Learning towards students’ learning motivation and concept understanding at the VIII Grade students’ of SMPN 2 Tanjung.